Mrtvo drevje v pragozdu Pečka - Debeljak, Marko (Zbornik gozdarstva in lesarstva, 1999)
This study treats dead trees and their remnants in the research areas of the Pe~ka virgin forest at a location of Abieti-Fagetum dinaricum. It covers four decaying stages: stump, mound, wood remnants, standing dead trees and their remnants. We first classify and describe the decaying stages, and define a manner of calculating their specific volume. We then compare the decaying stages, establishing regularities in the decaying process for the beech and the fir tree. Moreover, a quantitative comparison with living trees in the research area is performed. The research results show the major significance of the presence of dead trees for the complexity of the wood ecosystem reachedthrough evolutionary processes to be maintained
Keywords: biomasa; drevje; ecology; ekologija; pragozd; Slovenia; Slovenija